2018
DOI: 10.1167/iovs.17-22925
|View full text |Cite
|
Sign up to set email alerts
|

Diquafosol Sodium Inhibits Apoptosis and Inflammation of Corneal Epithelial Cells Via Activation of Erk1/2 and RSK: In Vitro and In Vivo Dry Eye Model

Abstract: PURPOSE. To evaluate the effect of diquafosol on corneal epithelium in a dry eye model using Transwell culture and a scopolamine-induced dry eye rat model. METHODS. Desiccation stress induced in an in vitro dry eye model using human corneal epithelial cells was used, and the cells were incubated with or without diquafosol media diluted at 1:100. Reactive oxygen species (ROS) generation was measured using 2 0 ,7 0dichlorofluorescein diacetate (DCFH-DA). Apoptosis was analyzed, and levels of phosphorylated Erk1/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 34 publications
2
25
0
2
Order By: Relevance
“…Our f indings demonstrate that hyperosmotic stress induces inflammation, and diquafosol is an effective agent that protects HCECs from hyperosmotic stress-induced inflammation. These results are consistent with previous studies in which the secretion of inf lammatory cytokines was signif icantly reduced in desiccation stress-induced dry eye models [25]. Results showing that diquafosol inhibits the production of inflammatory cytokines in a variety of dry eye models suggest that diquafosol may exert anti-inf lammatory effects on various pathogenic factors associated with dry eye syndrome, such as tear hyperosmolarity or dry conditions.…”
Section: Discussionsupporting
confidence: 92%
“…Our f indings demonstrate that hyperosmotic stress induces inflammation, and diquafosol is an effective agent that protects HCECs from hyperosmotic stress-induced inflammation. These results are consistent with previous studies in which the secretion of inf lammatory cytokines was signif icantly reduced in desiccation stress-induced dry eye models [25]. Results showing that diquafosol inhibits the production of inflammatory cytokines in a variety of dry eye models suggest that diquafosol may exert anti-inf lammatory effects on various pathogenic factors associated with dry eye syndrome, such as tear hyperosmolarity or dry conditions.…”
Section: Discussionsupporting
confidence: 92%
“…Inhibiting tear secretion by systemic administration of the muscarinic cholinergic antagonist scopolamine produced keratoconjunctivitis sicca that mimics human dry eye. This scopolamine-induced dry eye model is commonly used animal model in DED research [22,[24][25][26][27]. We demonstrated that the oxidation product 8-OHdG accumulated in the corneal epithelial cells of this model.…”
Section: Plos Onementioning
confidence: 73%
“…At present, the main clinical application of tear substitutes to relieve dry eye symptoms, but cannot effectively cure dry eye syndrome 3 . Inflammatory response, apoptosis, and changes in sex hormone levels are all associated with the development of dry eye syndrome, and inflammation is considered to be the most important factor in the pathogenesis of dry eye syndrome 4,5 …”
Section: Introductionmentioning
confidence: 99%
“…3 Inflammatory response, apoptosis, and changes in sex hormone levels are all associated with the development of dry eye syndrome, and inflammation is considered to be the most important factor in the pathogenesis of dry eye syndrome. 4,5 Interleukin-1 receptor-associated kinase 1 (IRAK1) is a serinethreonine kinase that mediates Toll-like receptors (TLR) and IL-1 signaling pathways. These signaling pathways are critical for regulating immune responses and inflammatory processes.…”
mentioning
confidence: 99%